Left Bundle Branch Area Pacing in a Giant Atrium With Atrial Standstill: A Case Report and Literature Review - Zheng, Jing; Yang, Qingye; Zheng, Jiasheng; Chen, Qiang; Jin, Qizhi (Frontiers in Cardiovascular Medicine, 2022)
Atrial standstill (AS) is a rare condition defined by the lack of atrial electrical and mechanical activity. It is usually clinically manifested as symptomatic bradycardia which requires permanent pacemaker (PPM) implantation. Traditional right ventricular apical pacing causes electrical and mechanical dyssynchrony resulting in left ventricular dysfunction, heart failure and arrhythmias. As a novel physiological pacing strategy, left bundle branch area pacing (LBBaP) has been demonstrated the effectiveness and safety in recent years, but its application in exceptional conditions is rarely reported. We report the case of a 47-year-old female who was diagnosed as AS complicated with a giant atrium, and recived a single-chamber PPM with LBBaP successfully.